The role of interpersonal communication in the formation of social relationships of Student at the Islamic University of Indonesia in the digital era - Vira Amelia; Dani Fadillah (Universitas Ahmad Dahlan, 2025)
The development of the digital era has changed the way students interact socially, but previous studies have focused more on digital communication practices and have not clearly explored the role of interpersonal communication in shaping social interactions. This gap highlights the need to understand how interpersonal interactions, both face-to-face and through digital media, influence students' social relationships. This study aims to analyze the role of interpersonal communication in shaping the social interactions of students at the Islamic University of Indonesia in the digital era. This study uses a qualitative approach with in-depth interviews as a data collection technique. It involved three students from different backgrounds as research informants. The results of this study indicate that face-to-face communication is more effective in shaping social interactions than digital communication. The theoretical contribution of this study lies in expanding the understanding of the role of interpersonal communication in the digital context, enriching the literature on student social communication, while the practical contribution is to provide recommendations for universities to design interaction strategies that can strengthen social engagement in the digital era.